Mineralogical, geochemical, spectroscopic, and color-making elements investigation of agate and chalcedony mineralization; case study: Kasrab district, east Iran - Mohammadreza Hosseinzadeh; Ali Asadi; Vartan Simmonds; Matthew I. Leybourne (Geochemistry, 2026)

The Jalilabad copper deposit in the Tarom-Hashjin magmatic belt, NW Iran:Epithermal or porphyry deposit? Evidence from geology, alteration, geochemistry, fluid inclusions, and stable isotope studies - Mohammadreza Hosseinzadeh; Ali Asadi; Vartan Simmonds; Matthew I. Leybourne; Mohsen Moayyed; Yalda Vahed (Acta Geochimica, 2025)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Polar Climate Change as Manifest in Atmospheric Circulation - J. A. Screen; T. J. Bracegirdle; I. Simmonds (Current Climate Change Reports, 2018)

On the dynamics of a case study of explosive cyclogenesis in the Mediterranean - J. Kouroutzoglou; H. A. Flocas; M. Hatzaki; K. Keay; I. Simmonds; A. Mavroudis (Meteorology and Atmospheric Physics, 2015)

A high-resolution climatological study on the comparison between surface explosive and ordinary cyclones in the Mediterranean - J. Kouroutzoglou; H. A. Flocas; M. Hatzaki; K. Keay; I. Simmonds (Regional Environmental Change, 2014)

Molecular marker-based characterization of a set of wheat genotypes adapted to Central Europe - V. Oslovičová; J.R. Simmonds; J.W. Snape; Z. Gálová; Z. Balážová; I. Matušíková (Cereal Research Communications, 2014)

Vertical characteristics of cyclonic tracks over the eastern Mediterranean during the cold period of the year - H. A. Flocas; P. Kountouris; J. Kouroutzoglou; M. Hatzaki; K. Keay; I. Simmonds (Theoretical and Applied Climatology, 2013)

Climatological aspects of explosive cyclones in the Mediterranean - J. Kouroutzoglou; H. A. Flocas; K. Keay; I. Simmonds; M. Hatzaki (International Journal of Climatology, 2011)
An objective climatology of explosive cyclones is performed over a 40‐year period (1962–2001), for the Mediterranean region with the aid of the Melbourne University automatic cyclone finding and tracking scheme. The major temporal and spatial characteristics of Mediterranean explosive cyclones are investigated, including frequency, movement, generation and dissipation, scale, depth, and intensity. It was verified that the explosive cyclogenesis in the Mediterranean is a rather rare phenomenon that occurs mainly from November to March. Explosive cyclones preferentially form along the northern Mediterranean coast, with maximum density in the Ligurian and Aegean Seas. The cyclogenesis mechanism that predominates in their development is characterized by an interaction of a short and an open long wave in a pre‐existing development (referred to as the KF mechanism). There are distinct differences between Western Mediterranean and Eastern Mediterranean explosive cyclones. Although explosive cyclones tend to form in the Western Mediterranean, their scale and depth is greater in the Eastern Mediterranean. Explosive cyclones more likely move from the main cyclogenetic areas in the Western Mediterranean along specific eastward paths over southern Italy and the Ionian Sea where they dissipate or they generate in Eastern Mediterranean and move north‐eastwards to the Black Sea or eastwards to Cyprus and Middle East. Copyright © 2010 Royal Meteorological Society

Impact of changing climate and land use on the hydrogeology of southeast Australia ∗ - I. Cartwright; I. Simmonds (Australian Journal of Earth Sciences, 2008)

Simulated Antarctic precipitation and surface mass balance at the end of the twentieth and twenty-first centuries - G. Krinner; O. Magand; I. Simmonds; C. Genthon; J. -L. Dufresne (Climate Dynamics, 2006)

Surface fluxes of momentum and mechanical energy over the North Pacific and North Atlantic Oceans - I. Simmonds; K. Keay (Meteorology and Atmospheric Physics, 2002)

Associations between varying magnitudes of the urban heat island and the synoptic climatology in Melbourne, Australia - C.J.G. Morris; I. Simmonds (International Journal of Climatology, 2000)

Synoptic comparison of cold events in winter and summerin Melbourne and Perth - I. Simmonds; T. Richter (Theoretical and Applied Climatology, 2000)

Molecular Evidence of Nosocomial Transmission of Hepatitis C Virus in a Haemodialysis Unit - Y. H. Abacioglu; F. Bacaksiz; I. H. Bahar; P. Simmonds (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Classification, nomenclature, and database development for hepatitis C virus (HCV) and related viruses: proposals for standardization - B. Robertson; G. Myers; C. Howard; T. Brettin; J. Bukh; B. Gaschen; T. Gojobori; G. Maertens; M. Mizokami; O. Nainan; S. Netesov; K. Nishioka; et al. (Archives of Virology, 1998)

Decadal and centennial variability of the southern semiannual oscillation simulated in the GFDL coupled GCM - I. Simmonds; D. J. Walland (Climate Dynamics, 1997)

Correction: Persistence characteristics of Australian rainfall anomalies - I. SIMMONDS; P. HOPE (International Journal of Climatology, 1997)

Correction: Persistence characteristics of Australian rainfall anomalies - I. SIMMONDS; P. HOPE (International Journal of Climatology, 1997)

Association between modes of variability of January Northern Hemisphere snow cover and circulation - D. J. Walland; I. Simmonds (Theoretical and Applied Climatology, 1997)

Biological control of snails exerted byEuglandina rosea (Ferussac) in Bermuda - F. J. Simmonds; I. W. Hughes (BioControl, 1963)